1982
DOI: 10.1113/jphysiol.1982.sp014375
|View full text |Cite
|
Sign up to set email alerts
|

Fibre types in chicken skeletal muscles and their changes in muscular dystrophy

Abstract: SUMMARY1. Five major fibre types in chicken skeletal muscles are recognized, based upon their histochemical and morphological characteristics. A classification of these which is readily related to a commonly used classification of mammalian muscle fibre types is given.2. Seven muscles of the chicken were analysed in recognizing this range of fibre types. The proportions of the different types in each of these were determined. In some cases a gradient of fibre type composition exists across a single muscle.3. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
2
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 45 publications
8
102
2
2
Order By: Relevance
“…Alkali pre-incubation was at pH 10.3 and 10.4. The fibers were typed according to Barnard et al (1982). …”
Section: Histochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Alkali pre-incubation was at pH 10.3 and 10.4. The fibers were typed according to Barnard et al (1982). …”
Section: Histochemistrymentioning
confidence: 99%
“…In the anterior region of this principally "slow tonic" muscle (Barnard et al, 1982), a mixture of fast and slow fibers has been found (Zhang et al 1985;Crow et al, 1983). In contrast to Zhang et al (1985), we found a majority of the slow fibers in the muscle's most anterior part to be of Type I instead of Type 111, based on the nomenclature of Barnard et al (1982), because after acid preincubation their myofibrillar ATPase reaction was stronger than that of Type 111 fibers (Figure 4e) and after alkali pre-treatment it was extinguished (not shown). Type I1 fibers in MA were of IIA subtype, based on their strong NADH tetrazolium reductase stain (Barnard et al, 1982) (Figure 4f).…”
Section: Fiber Tjpe-speczj5c Localization Of Fast Myosin Light Chain mentioning
confidence: 99%
“…One possible explanation is that the effect of dietary MNB on the skeletal muscle weight was different between muscle fiber types in the chicks. There is evidence that more than 99% of muscle fiber in the breast muscle is type II B fiber (Barnard et al, 1982). On the other hand, thigh muscles consist of several types of muscle fiber including type I, II A, II B, III A, and III B.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebrate skeletal muscle is composed of a heterogeneous population of exuafusal fibers, each of which is characterized by unique morphological, physiological, and biochemical properties (2,3,9,16,17). The current model for the way this diversity of fiber type is produced during development in avian muscle proposes that differentiation is initially under myogenic control, with different fiber types being derived from distinct myoblast cell lineages, but that continued differentiation in the late embryonic and post-hatch period becomes dependent on a variety of factors external to the muscle cell, such as innervation, hormones, and interactions with the extracellular matrix (25,29,34).…”
Section: Introductionmentioning
confidence: 99%